Larval trypanorhynch (Cestoda) infecting Euphausia americana (Euphausiacea) collected in the Mexican Caribbean Sea - David González Solís; Iván Castellanos Osorio; Ian Beveridge (Revista Mexicana de Biodiversidad)
Euphausiids are marine pelagic crustaceans widely distributed in all latitudes and oceans of the world.They are parasitized by a wide spectrum of parasite species. Cestodes of the Order Trypanorhyncha are endoparasitichelminths that as adults exclusively parasitize elasmobranchs and use euphausiids, and other planktonic crustaceans,as paratenic or intermediate hosts. From a zooplankton sample collected in Banco Chinchorro, Mexican CaribbeanSea, at depth of 941.2 m, one male of Euphausia americana was infected with a plerocercoid with a blastocyst of atrypanorhynch larval cestode hosted in the cephalothorax, which was identified as Eutetrarhynchidae gen. sp. Thisis the first record of a trypanorhynch larval cestode in Euphausia americana and the first geographical report in theCaribbean coast of Mexico.